Pelaksanaan Pendidikan Politik Di Kota Banda Aceh Pasca Lahirnya Undang-Undang Nomor 2 Tahun 2008 Tentang Partai Politik - Muhammad Heikal Daudy; Hamzah Hamzah (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Article 11 paragraph (1) letter a of Law Number 2 of 2008 on Political Parties, states that political parties function as a means of political education for members and the wider community to become Indonesian citizens who are aware of the rights and obligations in the life of society, nation, and state. The implementation of political education by political parties in the city of Banda Aceh is carried out through methods of coaching, socializing, and social activities. The inhibiting factor is the persistence of negative views from the public towards political parties, communication that is not established between the Regional Representative Council and the Regional Representative Council which is the spearhead of the implementation of political education, limited facilities and infrastructure as supporting factors for the implementation of political education. Political parties are expected to continue to provide political education to the community on an ongoing basis in order to be able to change the paradigm or mind set of the community towards the party.